7 Diagnostic accuracy of 12 lead ECG Q-waves as a marker of myocardial scar: validation with CMR. (26th April 2015) - Carpenter, Alexander; Dastidar, Amardeep Ghosh; Wilson, Catherine; Rodrigues, Jonathan; Baritussio, Anna; Lawton, Chris; Palazzuoli, Alberto; Ahmed, Nauman; Townsend, Mandie; Baumbach, Andreas; Nightingale, Angus; Bucciarelli-Ducci, Chiara
Abstract : Background: Traditionally, the presence of Q-waves on 12 lead ECG is considered a marker of a large and/or transmural myocardial infarction (MI). Late gadolinium enhancement (LGE) cardiovascular magnetic resonance (CMR) accurately identifies the presence and extent of myocardial infarction and has become the gold standard for the assessment of myocardial viability. Aim: To determine the diagnostic accuracy of Q-waves on 12 lead ECG to identify myocardial scarring as compared with CMR. Methods: Data was collected on 631 consecutive patients referred for a stress CMR with suspected ischaemic heart disease (April 2013 to Mar 2014). A 12-lead ECG was recorded. Pathological Q-waves – deflection amplitude of >25% of the subsequent R wave, or being >0.04 s (40 ms) in width and >2 mm in amplitude in >1 corresponding lead. A comprehensive CMR protocol was used. Transmural infarction was defined as >50% LGE. Results: 498 patients were included (mean age of 64 ± 12 years, 71% males). 290 patients demonstrated MI of whom 157 were transmural and 133 sub-endocardial based on CMR LGE. 126 had pathological Q-waves on 12 lead ECG. The sensitivity, specificity, positive, negative predictive value and accuracy of 12 lead ECG Q-wave as a marker of transmural MI was 36%, 80%, 45%, 73% with moderate overall diagnostic accuracy (66%). The diagnostic accuracy of Q waves as a predictor of previous MI (composite of sub-endocardial and transmural) was 55% (Table 1 ). Conclusion: Our study demonstrates that the presence of pathological Q-waves on 12 lead ECG is not only a poor marker of myocardial scarring, but also a poor predictor of viability when compared to CMR. In their clinical decision making process, clinicians needs to be aware of the limitation of ECG Q-waves.